Perception of people with intellectual disabilities by residents of the Tarnów region, Poland - Weronika Gieniec; Beata Jurkiewicz (University of Applied Sciences in Tarnow, Poland, 2023)
Introduction: Social perception of disability is often a more serious problem than the disability itself. Acceptance of people with disabilities by the social environment is crucial, as it promotes their all-round development better than measures taken in individual rehabilitation. The aim of the study was to analyze the perception of people with intellectual disabilities by residents of the Tarnów region. Material and methods: The study was conducted by a diagnostic survey method using the author's survey questionnaire in March-May 2023. 314 correctly completed questionnaires were included in the study, completed by people between 18 and 67 years of age (mean 25.97 ± 7.97 years). A significance level of p < 0.05 was adopted. Results: As many as 32.48% (n = 102) of the respondents admit that they have a person with intellectual disabilities in their family or neighborhood. Among the respondents, 54.14% are familiar with local organizations for people with intellectual disabilities and their families, where 17.20% of people admitted that they have done volunteer work for such an organization. A willingness to become a volunteer for such an organization was expressed by 44.90% of people. Respondents overwhelmingly agreed that people with intellectual disabilities should participate in the life of the local community (91.40%). The majority of respondents (79.62%) believe that intellectually disabled people have the same sexual needs as the rest of society, followed by 15.61% who say they have no sexual needs, and 2.87% associate the sexual needs of intellectually disabled people with their degree and type of disability. Conclusions: Society shows signs of effortless tolerance - it does not want to have closer relations with people with intellectual disabilities, but at the same time does not mind that such people participate in society. Respondents show insufficient knowledge of the sexuality of people with intellectual disabilities.